Alkali activation of waste concrete powder: Effects of alkali type and concentration. Issue 10 (15th May 2023) - Sasui, Sasui; Kim, Gyuyong; Nam, Jeongsoo; Alam, Syed Fakhar; Eu, Hamin; Lee, Yaechan; Ahmad, Mahmood
Abstract: Concrete is a conventional material widely used for decades to build infrastructures. Consequently, a significant amount of waste concrete is being generated. Alkali activation of waste concrete powder (WCP) is a sustainable approach for efficiently recycling waste concrete to produce alkali-activated cement. Accordingly, this study recycled waste concrete by alkali activation of WCP. The effects of two alkali activators (NaOH and KOH) of various concentrations on the performance of alkali activated WCP cement were discussed. The synthesized samples were cured at room temperature for up to 28 days and then compressive strength test was performed. The samples were then characterized by Fourier transform infrared (FT-IR) spectroscopy, X-ray powder diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS). It was found that the NaOH-activated WCP outperformed the KOH-activated WCP. Moreover, activation by 8 M alkali solutions improved the compressive strength, microstructure, and reactivity of WCP. The findings of this study are significant for developing alkali-activated cement using waste concrete powder.